Identification of Novel Protein Biomarkers and Drug Targets for Acne Vulgaris by Integrating Human Plasma Proteome with Genome-Wide Association Data - Xu D; Yang X; Wu W; Yang J (Dove Medical Press, 2024)
Dongrui Xu,1,* Xiaoyi Yang,1,* Wenjuan Wu,2 Jiankang Yang1 1School of Basic Medical Sciences, Dali University, Dali, Yunnan, People's Republic of China; 2Department of Dermatology, First Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, People's Republic of China*These authors contributed equally to this workCorrespondence: Jiankang Yang, School of Basic Medical Sciences, Dali University, Dali, Yunnan, People's Republic of China, Email jkyang1984@126.com Wenjuan Wu, Department of Dermatology, First Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, People's Republic of China, Email wuwj1021@126.comBackground: Despite the availability of numerous therapies, the treatment of acne vulgaris remains challenging. Novel drug targets for acne vulgaris are still needed.Methods: We conducted a Mendelian randomization analysis to explore possible drug targets for acne vulgaris. We utilized summary statistics obtained from the dataset of acne vulgaris, including 399,413 individuals of European ancestry. We gathered genetic instruments for 566 plasma proteins from genome-wide association studies. In order to strengthen the findings from Mendelian randomization, various methods were employed, including bidirectional Mendelian randomization analysis, Bayesian co-localization, phenotype scanning, and single-cell analysis. These methods facilitated the identification of reverse causality, the search for reported variant-trait associations, and the determination of the cell types that is the primary source of protein. Furthermore, using the plasma proteins in the deCODE cohort, we conducted a replication of the Mendelian randomization analysis as an external validation.Results: At the significance level of Bonferroni (P < 8.83× 10− 5), a protein-acne pair was discovered through Mendelian randomization analysis. In plasma, increasing TIMP4 (OR = 1.15; 95% CI, 1.09- 1.21; P = 1.01× 10− 7) increased the risk of acne vulgaris. The absence of reverse causality was observed in the TIMP4 protein. According to Bayesian co-localization analysis, TIMP4 shared the same variant with acne vulgaris (PPH4 = 0.93). TIMP4 was replicated in deCODE cohort (OR = 1.17; 95% CI, 1.10- 1.24; P = 1.48× 10− 7). Single-cell analysis revealed that TIMP4 was predominantly detected in myeloid cells in blood, and was detected in almost all cell types in skin tissue.Conclusion: The integrative analysis revealed that the level of plasma TIMP4 has a direct influence on the risk of developing acne vulgaris. This implies that TIMP4 protein could serve as a potential target for the development of drugs aimed at treating acne vulgaris.Keywords: plasma proteome, acne vulgaris, drug target, biomarker, Mendelian randomization, TIMP4